New fossil insect order Permopsocida elucidates major radiation and evolution of suction feeding in hemimetabolous insects (Hexapoda: Acercaria) - Huang, Di-Ying; Bechly, Günter; Nel, Patricia; Engel, Michael S; Prokop, Jakub; Azar, Dany; Cai, Chen-Yang; van de Kamp, Thomas; Staniczek, Arnold H; Garrouste, Romain; Krogmann, Lars; Dos Santos Rolo, Tomy; et al. (Scientific reports, 2016)
With nearly 100,000 species, the Acercaria (lice, plant lices, thrips, bugs) including number of economically important species is one of the most successful insect lineages. However, its phylogeny and evolution of mouthparts among other issues remain debatable. Here new methods of preparation permitted the comprehensive anatomical description of insect inclusions from mid-Cretaceous Burmese amber in astonishing detail. These "missing links" fossils, attributed to a new order Permopsocida, provide crucial evidence for reconstructing the phylogenetic relationships in the Acercaria, supporting its monophyly, and questioning the position of Psocodea as sister group of holometabolans in the most recent phylogenomic study. Permopsocida resolves as sister group of Thripida + Hemiptera and represents an evolutionary link documenting the transition from chewing to piercing mouthparts in relation to suction feeding. Identification of gut contents as angiosperm pollen documents an ecological role of Permopsocida as early pollen feeders with relatively unspecialized mouthparts. This group existed for 185 million years, but has never been diverse and was superseded by new pollenivorous pollinators during the Cretaceous co-evolution of insects and flowers. The key innovation of suction feeding with piercing mouthparts is identified as main event that triggered the huge post-Carboniferous radiation of hemipterans, and facilitated the spreading of pathogenic vectors.
Keywords: Insecta; zkameněliny; fylogeneze; záření; Phylogeny; Ecology; Fossils; biologická evoluce; pyl; jantar; Pollen; Animals; Biological Evolution; ekologie; hmyz; zvířata; Magnoliopsida; Amber; Radiation